Helping your pupils to think for themselves - Wilson, Jeni.; Murdoch, Kath. (London ; New York : Routledge, 2008)
Examines three broad categories of thinking, including reflective and metacognition, creative, and logical and critical, discusses metacognition as the most important type of thinking for students, offers advice to teachers on how to audit their pupils' thinking skills, and provides activities and strategies for helping students develop independent thinking skills.
"A David Fulton book"--Cover p. [4].
Includes bibliographical references (p. 64-65).
Professional
Professional
Keywords: Creative thinking -- Study and teaching; Critical thinking -- Study and teaching; Creative thinking -- Study and teaching; Critical thinking -- Study and teaching